Morphological, Anatomical, and Phytochemical Responses of Celosia argentea to Light Intensity - Carlen Fredella Josenia; Tia Setiawati; Marheny Lukitasari; Rusdi Hasan (UNIVERSITAS PGRI MADIUN, 2025)
This study investigates the phytochemical content and morpho-anatomical characteristics of Celosia argentea L. plants grown under different light intensities in the Embung Leuwi Padjadjaran area. Leaf samples were collected from shaded and unshaded locations to compare their responses to varying light conditions. Phytochemical analysis revealed that plants in higher light intensity areas tended to have increased levels of specific phytochemical compounds, which is crucial for the plant's defense mechanisms. Furthermore, the research found morphological and anatomical differences, such as greater leaf thickness and a lower stomatal density in unshaded plants. Conversely, shaded plants exhibited higher chlorophyll content and larger leaf areas, which are adapted to low-light environments. The study concludes that varying light intensity significantly influences the morpho-anatomical features and phytochemical composition of Celosia argentea L., with shaded conditions promoting adaptations for light capture and unshaded conditions increasing certain phytochemicals and leaf thickness.